Pengaruh Intellectual Capital dan Kinerja Keuangan terhadap Manajemen Laba pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2018 – 2021 - Ardiansyah, Nabiila Putri; Sadikin, Dikdik Saleh (STIE Indonesia Banking School, 2023)
This study aims to determine the effect of Intellectual Capital and Financial Performance on Earnings Management in food and beverage companies for the period 2018–2021. This study used 28 food and beverage companies listed on the Indonesia Stock Exchange using a purposive sampling method. Hypothesis testing was carried out in this study using descriptive statistics using panel data regression analysis method. The results of this study indicate that Intellectual Capital has a positive effect on Earnings Management. Meanwhile, financial performance proxied by Return on Assets (ROA) has a negative effect on Earnings Management.